2020
DOI: 10.3354/meps13199
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of salmon lice on mortality, marine migration distance and premature return in sea trout

Abstract: Brown trout Salmo trutta (L.) is a facultative anadromous species, where a portion of individuals in populations with access to the sea perform migrations to use the richer feeding resources. We investigated the effect of salmon lice Lepeophtheirus salmonis (Krøyer 1837) infestation on the survival and behaviour of wild trout post-smolts (average fork length = 180 mm) during their marine migration. Comparisons of the marine migratory behaviour were made between an artificially infested group (n = 74) and a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Our study found limited evidence of sea trout shortening or temporarily suspending their marine residence by re‐entering freshwater habitats before returning to the sea (Birkeland & Jakobsen, 1997; Serra‐Llinares et al ., 2020). In contrast, brief marine stays (<1 day) immediately prior to or after a marine stay of longer than 7 days occurred more frequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found limited evidence of sea trout shortening or temporarily suspending their marine residence by re‐entering freshwater habitats before returning to the sea (Birkeland & Jakobsen, 1997; Serra‐Llinares et al ., 2020). In contrast, brief marine stays (<1 day) immediately prior to or after a marine stay of longer than 7 days occurred more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Migration behaviour may also modify L. salmonis infestations on sea trout. For instance, individuals which migrate to areas without salmon farms, those that make brief returns to fresh or brackish water and/or individuals with shorter overall marine residence durations may benefit from lower exposure to L. salmonis infective stages (Diserud et al ., 2020; Serra‐Llinares et al ., 2020). Low salinity waters reduce the survival of L. salmonis (Andrews & Horsberg, 2020; Bricknell et al ., 2006), in addition to reducing the effects of lice‐induced osmotic stress to infected trout (Birkeland & Jakobsen, 1997; Wells et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…the ectoparasitic copepods Lepeophtheirus salmonis , infect salmonids when they leave freshwater habitats and migrate out to sea. In anadromous populations of brown trout, Salmo trutta , that migrate to coastal waters to feed for a few months before returning to river habitats, experimental infection with sea lice caused increased mortality, while infected fish that survived stayed closer to estuaries and returned prematurely to fresh waters (Serra‐Llinares et al ., 2020). Lice‐infected pink salmon, Oncorhynchus gorbuscha , had reduced endurance for prolonged swimming compared to uninfected control fish, but only when infected by large female lice (Mages & Dill, 2010).…”
Section: Parasites As a Cost During Migrationmentioning
confidence: 99%
“…In areas with open net cage farming of Atlantic salmon Salmo salar L. 1758, the density of salmon lice can increase by orders of magnitude, to levels that harm wild salmonids (Bøhn et al ., 2020; Krkošek et al ., 2011; Thorstad et al ., 2015). Although sea trout populations can cope with the parasite at natural levels, infections exceeding a certain threshold level increase mortality and reduce individual growth, either directly though physiological processes or indirectly via premature returns to fresh water (Serra‐Llinares et al ., 2020; Thorstad et al ., 2015). In Norway, open net cage farming of salmon occurs along almost the entire coast, with the highest activity in the south‐western and central parts where numerous sea trout populations are declining (Anon, 2019).…”
Section: Introductionmentioning
confidence: 99%